Genetic parameters for agronomic characteristics: II: intermediate and advanced stages in a Open Access potato seed breeding population - Ortíz, R.; Golmirzaie, A.M. (2003)
The aim of this research was to determine the genetic variation available in some important characteristics for true potato seed breeding in intermediate and advanced stages of a breeding population developed by the Centro Internacional de la Papa. A factorial mating design was used to calculate variance components and heritability at both selection stages. Four males were crossed with four females within each set (4 for intermediate stage and 5 for advanced stage) and their resulting offspring tested across two contrasting locations. Tuber yield and set were the only common characteristics recorded in both selection stages. In the intermediate stage early development characteristics (seed germination plus root and internode length) were also measured. In the advanced breeding material, vine earliness and other reproductive traits (days to flowering, flowering intensity, style length and pollen production) were scored. The heritability for tuber yield (0.35) and tuber set (0.32) in the advanced selection stage was higher than in the intermediate stage (0.26 and 0.13 respectively), which suggest that recombination through more cycles of recurrent selection brought untapped variation for both characteristics in this breeding material. Significant additive genetic variation, and thereby high heritability, was observed for internode length (0.52) in the intermediate selection stage, and for days to flowering (0.53) in the advance stage. Progress through selection may be expected for both characteristics. The heritability for pollen production was intermediate (0.23), while it was low (i.e. 0.10) for the other characteristics recorded in both populations.